(untitled) (Journal of Computational Mathematics, 2021)
In this paper we present two algorithms for LC^1 unconstrained optimization problems which use the second order Dini upper directional derivative. These methods are simple and easy to perform. We discuss the related properties of the iteration function, and establish the global and superlinear convergence of our methods.